Artificial Intelligence in Teaching Islamic Studies: Challenges and Opportunities - Hakim, Abdul; Anggraini, Pauli (Molang: Journal Islamic Education, 2023)
The main goal of this research will be to establish how AI technology could apply to learning Islamic education and provide more critical evidence about the challenges and opportunities posed by integrating AI into such learning. In this regard, the applicability of AI and associated challenges in teaching Islamic Studies is being explored through a systematic review of literature. Different databases such as Scopus, ERIC, and Google Scholar were utilized to locate literature. Results from the identifications were thematically analyzed based on patterns, similarities, and differences among studies. Studies conducted on the current topic evidenced that AI can create multiple possibilities that will influence accelerated student development and help the teaching process to come closer to what teachers seek: satisfying and engaging tasks. Moreover, AI holds an immense opportunity to help or increase the development of pedagogical approaches for academics within their own professional perspectives and experiences. However, some of the challenges that must be addressed with care are ethical considerations and data privacy. This study is bound to add to the literature on how AI has been applied in teaching Islamic Studies, especially from the sociocultural perspective. The findings of this study are also expected to provide valuable insights for educational practitioners and researchers in the field, while helping to improve the understanding and application of religious values in daily life.